Business readiness for dual transformation: an analysis of business capabilities for digital and sustainable transformation - Encinas Grijalva, María del Socorro; Olivieri-Sangiacomo, Flavio Arturo; Galván Vela, Esthela; Ravina-Ripoll, Rafael (My University, 2024)
In a dynamic business environment, the convergence of Digital Transformation and Sustainable Transformation has emerged as a comprehensive strategy for companies seeking to thrive in the modern era. For this transformation to successfully develop, the appropriate conditions must be present to carry out a process of digitisation and sustainability. Therefore, this research aimed to identify the readiness level of companies established in the city of Tijuana, Mexico, to adopt a dual transformation process. An analysis of the different digital and sustainable transformation models was carried out, and a self-diagnosis model was designed. Then, a quantitative instrument was applied to a sample of 148 small, medium and large companies in Tijuana between 2022 and mid-2023. The analysis consisted of a descriptive analysis of the data and a correlation analysis. It concludes that the elements that most explain the dual transformation are strategy, culture, organisational and technical capabilities. Likewise, the related factors are definition and communication, alignment, and scope of the objectives within the strategy; change management, knowledge and collaboration in the culture; within the organisation: leadership, processes and organisational structure; and finally in the technical capabilities data management, training and systems integration. The results of this research allowed us to identify and propose strategies to implement the dual transformation and increase the scalability and competitiveness of the adopting companies.
Keywords: Digital transformation; Sustainable transformation; Organisational strategies; Campus Tijuana